Investor-expert interaction model in the innovation investment system with knowledge asymmetry - Zaur Z. Ivanov, Alim O. Gurtuev; Derkach, Elena G.; Kazancheva, Halimat K.; Dumanova, Aminat Kh. (Opción, 2019)
The mechanisms of investing in innovation projects, when an objective evaluation of a project is impossible due to inherent uncertainty are subjects of increasing interest. As a method, the toolkit of non-cooperative games with communication is widely used in economics to model situations of information asymmetry. We propose a model of investor-expert interaction in the system of innovation investment. The model is a recurring game with imperfect information, deferred revenues and Bayesian re-evaluation of players’ own type.Different equilibria for some qualitatively different configurations of initial values of budgets, risk attitude, and distribution of player types are found.